Remifentanil does not increase urine output during oral surgery, contrary to its effect during other surgeries - a cohort study - Ouchi,Kentaro (2017)
Abstract Background: An increase in urine output by remifentanil injection during laparoscopic procedures and surgeries such as cardiac and gynecological procedures, due to suppression of the stress response to surgery, has been reported. The aim of our prospective, observational, cohort study was to assess the effect of remifentanil analgesia on urine output during dental and minor oral surgery by comparing intraoperative urine output under defined infusion volumes with and without the use of remifentanil. Methods: Dental patients aged 16 years or older, American Society of Anesthesiologists physical status 1, with no renal diseases or abnormal blood values of serum creatinine and BUN, not on treatment with diuretic drugs, and undergoing minor oro-maxillofacial surgery or dental treatment under inhalation general anesthesia were included in this study. Urethral catheterization was performed after anesthesia induction, and urine output was measured every 30 minutes. We measured urine volume (mL) and rate of urine output (mL.kg-1.h-1) intraoperatively, and compared these parameters between patients who did and did not receive remifentanil during the intraoperative period. Results: Eighty-seven patients were categorized into the remifentanil group (n = 43) or remifentanil non-use group (n = 44). Both volume of urine (mL) and rate of urine output (mL.kg-1.h-1) were not significantly different between the two groups (remifentanil group, 372.3 ± 273.5 mL, 1.8 ± 1.1 mL.kg-1.h-1; remifentanil non-use group, 343.3 ± 283.3 mL, 1.9 ± 1.2 mL.kg-1.h-1; p = 0.63; 0.57). Conclusion: Our results show that use of remifentanil during dental and minor oral surgeries does not increase urine output.